3D printing porous screw with gradient structure coating and preparation method of 3D printing porous screw

By forming a gradient structure coating on titanium alloy screws, the problem of single function in the prior art is solved, the combination of multiple biologically active functions is achieved, and the adaptability of biological materials in clinical applications is improved and Effect.

CN119424776AInactive Publication Date: 2025-02-14JILIN UNIVERSITY
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510025945.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing titanium alloy screws lack multiple structures and multiple biological activity functions in biomedical applications, making it difficult to meet the needs of complex and changeable clinical scenarios.

Method used

3D printed porous screws with gradient structure coating are used to form a three-layer gradient hydrogel system on the surface of the screw, which contains different concentrations of sodium alginate, determinated peptide type I collagen and divalent biologically active cations, respectively, to achieve cross-linking. Double gradient distribution of density and ion concentration.

Benefits of technology

This technical method shows a biomechanical stress gradient in terms of biomechanical properties, promotes the differentiation of tissue resident stem cells, and provides gradient biostress support, improving the adaptability and effect of biomaterials in clinical applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119424776A_ABST
    Figure CN119424776A_ABST
Patent Text Reader

Abstract

The invention is suitable for the technical field of biomedicine and high polymer materials, and provides a 3D printing porous screw with a gradient structure coating and a preparation method of the 3D printing porous screw. According to the invention, a cross-linked structure with double gradient distribution is designed, and bivalent bioactive cations with different concentrations are cross-linked with a sodium alginate solution to form a hydrogel system with biomechanical stress gradient. The system not only can promote the differentiation of tissue resident stem cells and provide gradient biological stress support, but also can maintain the ion biological activity concentration in the local environment of damaged tissues through slow-release ions, and promote blood supply recovery and anti-infection ability. Besides, the biocompatibility and the mechanical property of the hydrogel are enhanced by the de-telopeptide type I collagen doped in the system, so that the porous screw has excellent stability and cell ingrowth capability, thereby better adapting to complex clinical scenes, and improving the tissue repair effect and the clinical application value of biological materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomedicine and polymer materials, and in particular relates to a 3D printed porous screw with a gradient structure coating and a preparation method thereof. Background Art

[0002] In the current application field of bioactive materials, titanium alloy screws have played a significant role in promoting the development of orthopedic surgery and postoperative rehabilitation of patients with their excellent biocompatibility and biomechanical strength. For example, the Chinese patent with publication number CN118987338A discloses a method for preparing a titanium alloy surface coating with a single osteogenic activity based on polydopamine. However, titanium alloy screws usually show biological inertness during use. Although it can excellently fix various tissues, it lacks the promoting effect on tissue healing and bone tunnel repair, which also leads to the emergence of some clinical problems. For example, after anterior cruciate ligament reconstruction, patients often suffer from prosthesis infection and low return to sports rate due to the functional defects of simple titanium alloy screws. This reflects that the various biomaterials currently on the market have single functions and are difficult to adapt to the growing health needs of patients.

[0003] At the material research and development level, although with the development of polymer materials and corresponding functional metal materials, current bioactive materials can independently achieve functions such as promoting vascularization, antibacterial, and promoting bone tunnel healing (for example, Chinese patent publication number CN116870249B discloses the use of a polylactic acid-glycolic acid copolymer scaffold in promoting cartilage differentiation and regeneration), but in the face of complex and changing clinical scenarios, there is still a lack of materials with multiple structures and multiple bioactivities to meet market demand.

[0004] Therefore, how to develop a 3D printed porous screw with a gradient functional layer structure and a gradient structure coating that can achieve multiple bioactive functions has become a problem that technicians in this field need to solve urgently. To this end, the present invention proposes a 3D printed porous screw with a gradient structure coating and a preparation method thereof. Summary of the invention

[0005] The purpose of the present invention is to provide a 3D printed porous screw with a gradient structure coating and a preparation method thereof, aiming to solve the problems raised in the above-mentioned background technology.

[0006] The purpose of the present invention is achieved through the following technical solutions: A 3D printed porous screw with a gradient structure coating comprises a 3D printed porous screw and a bioactive component, wherein the bioactive component comprises sodium alginate, type I telopeptide collagen and divalent bioactive cations; wherein the mass fraction of the sodium alginate solution is divided into three gradients, namely 1.2-1.6%, 1.6-2.0% and 2.0-2.4%; the concentration of the type I telopeptide collagen solution is 0.5-1.5%; the concentration of the divalent bioactive cations is divided into three gradients, namely 0.008-0.012M, 0.013-0.017M and 0.018-0.022M; and the divalent bioactive cations are divalent copper ions.

[0007] A method for preparing a 3D printed porous screw with a gradient structure coating as described above comprises the following steps: Step S1: weighing materials according to the ratio; Step S2: fully dissolving sodium alginate and atelocollagen type I at the concentrations and mixing them to prepare a gradient concentration colloidal solution; Step S3: dissolving the divalent biologically active cations in double distilled water at the concentrations to prepare gradient concentration ion solutions; Step S4: According to the concentrations of the three bioactive components, a gradient hydrogel system is prepared, which is specifically divided into three layers: The first layer: 1.2~1.6% sodium alginate + 0.5~1.5% atelocollagen type I + 0.008~0.012M divalent bioactive cations; The second layer: 1.6~2.0% sodium alginate + 0.5~1.5% atelocollagen type I + 0.013~0.017M divalent bioactive cations; The third layer: 2.0~2.4% sodium alginate + 0.5~1.5% atelocollagen type I + 0.018~0.022M divalent bioactive cations; Step S5: preparing a 3D printed porous screw; Step S6: The gradient hydrogel system prepared in step S4 is wrapped on the surface of the 3D printed porous screw prepared in step S5, and freeze-dried at -80°C for 36 to 60 hours to complete the preparation of the 3D printed porous screw with a gradient structure coating.

[0008] Furthermore, in step S2, the specific steps of preparing the gradient concentration colloidal solution are as follows: Step S21: Take the atelo-type I collagen powder, add water to dissolve it, prepare a solution with a mass fraction of 0.5-1.5%, and stir it at 20-45° C. for 5-10 minutes until the solution is clear and transparent; Step S22: taking sodium alginate powder and adding it to the solution obtained in step S21 to prepare a solution with a mass fraction of sodium alginate of 1.2-1.6%; the specific operation is: fully stirring for 20-40 minutes at 20-45°C, adding powder while stirring, and after the powder is fully dissolved, centrifuging the solution until the solution is clear and transparent; Step S23: repeat step S22 to adjust the mass fraction of sodium alginate to 1.6-2.0%; Step S24: repeat step S22 to adjust the mass fraction of sodium alginate to 2.0-2.4%; Dissolution conditions were: magnetic stirrer 500-1000 rpm, 20-40 min; The centrifugation conditions were: 37°C, 2500 rpm, 5-10 min.

[0009] Furthermore, in step S3, the specific steps of preparing the gradient concentration ion solution are as follows: Step S31: taking a divalent biologically active cation powder, adding water to dissolve it, and preparing an ion solution with a concentration of 0.008-0.012M; Step S32: repeat step S31 to adjust the concentration to 0.008-0.012M; Step S33: Repeat step S31 to adjust the concentration to 0.018~0.022M.

[0010] Furthermore, in step S4, the specific steps of preparing the gradient hydrogel system are as follows: Step S41: inject 200-300 μL of the ion solution obtained in step S33 into a transparent cylindrical mold with a bottom diameter of 10-15 mm and a height of 25-35 mm, then add 500-800 μL of the colloidal solution obtained in step S24 into the mold, and let stand at 24-37° C. for 20-45 min to form a bottom layer of hydrogel; Step S42: adding 200-300 μL of the ion solution obtained in step S32 to the surface of the hydrogel obtained in step S41, and then adding 500-800 μL of the colloidal solution obtained in step S23, and standing at 24-37° C. for 20-45 min to form a second layer of hydrogel; Step S43: adding 200-300 μL of the ion solution obtained in step S31 to the surface of the hydrogel obtained in step S42, and then adding 500-800 μL of the colloidal solution obtained in step S22, and standing at 24-37° C. for 20-45 min to form a gradient hydrogel system; Step S44: placing the gradient hydrogel system obtained in step S43 into 2-2.5 mL of ultrapure water, ultrasonically vibrating for 5-10 min at 24-37° C., discarding the supernatant, and obtaining a pure gradient hydrogel system; Step S45: placing the gradient hydrogel system obtained in step S44 under ultraviolet light for sterilization; the environmental conditions for ultraviolet light irradiation are: temperature of 24-37° C., wind speed of 0.2-0.4 m / s, and irradiation time of 8-12 h.

[0011] Furthermore, in step S5, the specific steps of preparing the 3D printed porous screw are as follows: Step S51: Select the prepared PEI filaments, put them into an oven at 110-130° C., dry them for 2 hours, and then seal and store the dried PEI filaments; Step S52: According to the shape of the required screw, a pre-printed bracket structure model is established using a three-dimensional modeling software, and the model is converted into an STL file; the STL file is imported into the 3D printer system, and the print nozzle, print chamber and molding substrate of the 3D printer are preheated through the automatic temperature control system, and then the PEI wire is fed into the preheated print nozzle using an automatic wire feeding device. The print nozzle prints layer by layer according to the trajectory path generated by the software until the printing is completed to obtain a 3D printed porous screw; the obtained 3D printed porous screw is placed in an oven at 100-120°C and baked for 10-30 minutes.

[0012] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention forms a cross-linked structure by allowing different concentrations of divalent bioactive cations to be fully immersed in a sodium alginate solution. The structure presents a double gradient distribution of cross-linking density and ion concentration. In terms of biomechanical properties, this structure exhibits a biomechanical stress gradient generated according to the gradient change of cross-linking density, which is beneficial to promote the differentiation of tissue-resident stem cells at the interface of multiple tissue structure damage and provide gradient biostress support locally in the tissue.

[0013] 2. The gradient structure designed by the present invention from the perspective of bionics is closer to complex clinical scenarios. This structure can adapt to the repair needs of different tissues and promote tissue repair at different levels by carrying a variety of drugs or ions, thereby improving the adaptability and effectiveness of biomaterials in clinical applications.

[0014] 3. The present invention introduces divalent bioactive cations into the system, which not only promotes the formation of cross-linking gradients, but also realizes the sustained release of ions through the sodium alginate cross-linking system. This process is conducive to maintaining the bioactive concentration of ions in the local environment of damaged tissues, thereby promoting the recovery of local blood supply to damaged tissues, the ability to resist infection of graft prostheses, or accelerating bone tunnel healing.

[0015] 4. The present invention incorporates de-telopeptide type I collagen into the system to simulate the extracellular matrix components of most damaged tissues in the body, which not only enhances the biocompatibility of the hydrogel system and makes the healing process of damaged tissue closer to physiological healing rather than fibrous scar healing, but also enhances the cross-linking density and strength of the hydrogel layer, so that the porous screws with gradient structure coating have excellent stability.

[0016] 5. The porous structure screw in the present invention reduces the difficulty of cell growth and enhances the potential of cell proliferation and differentiation. This design further promotes the physiological healing process. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 Schematic diagram of the structure of the 3D printed porous screw with gradient structure coating in Example 1; (a) is a cross-sectional view of the coating, and (b) is a top view of the 3D printed porous screw with gradient structure coating.

[0018] Figure 2 The CCK proliferation biocompatibility test results of the 3D printed porous screws with gradient structure coating in Example 1.

[0019] Figure 3 is the maximum tensile load at the rat bone-tendon interface.

[0020] Figure 4 is the maximum tensile load at the rabbit bone-tendon interface. DETAILED DESCRIPTION

[0021] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.

[0022] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.

[0023] Example 1: A 3D printed porous screw with a gradient structure coating, comprising a 3D printed porous screw and a bioactive component, wherein the bioactive component comprises sodium alginate, copper sulfate, and de-telopeptide type I collagen; wherein the concentration of copper sulfate is divided into three gradients, namely 0.010 M, 0.015 M, and 0.020 M; the mass fraction of the sodium alginate solution is divided into three gradients, namely 1.5%, 1.8%, and 2.0%; and the concentration of the de-telopeptide type I collagen solution is 1.0%.

[0024] The preparation method of the 3D printed porous screw with the gradient structure coating comprises the following specific steps: Step S1: weighing materials according to the above-mentioned gradient hydrogel system; Step S2: fully dissolving sodium alginate and atelocollagen type I at the above concentrations and mixing them to prepare a gradient concentration colloidal solution; Step S3: dissolving 98% copper sulfate pentahydrate powder in double distilled water at the above concentration to prepare a gradient concentration ion solution; Step S4: According to the concentrations of the three bioactive components, a gradient hydrogel system is prepared, which is specifically divided into three layers: The first layer: 1.5% sodium alginate + 1.0% atelocollagen type I + 0.010M copper sulfate solution; The second layer: 1.8% sodium alginate + 1.0% atelocollagen type I + 0.015M copper sulfate solution; The third layer: 2.0% sodium alginate + 1.0% atelocollagen type I + 0.020M copper sulfate solution; Using the cross-linking effect of copper sulfate and sodium alginate, gradient hydrogel structures with different cross-linking densities and different ion concentrations at different levels were prepared. The cross-linking conditions were as follows: the colloidal solution and the ion solution were fully mixed in turn according to different levels, and allowed to stand at 37°C for 30 minutes to achieve full cross-linking; Step S5: preparing a 3D printed porous screw; Step S6: The gradient hydrogel system prepared in step S4 is wrapped on the surface of the 3D printed porous screw prepared in step S5, and freeze-dried at -80°C for 36 hours.

[0025] Wherein, in step S2, the specific steps of preparing the gradient concentration colloidal solution are as follows: Step S21: Take the atelo-type I collagen powder, add water to dissolve it, prepare a solution with a mass fraction of 1.0%, and stir it at 24° C. for 10 minutes until the solution is clear and transparent; Step S22: taking sodium alginate powder, adding it to the solution obtained in step S21, and dissolving it into a solution with a mass fraction of sodium alginate of 1.5%; the specific operation is: stirring thoroughly for 30 minutes at 24°C, adding the powder while stirring to avoid agglomeration of the sodium alginate powder, and after the powder is fully dissolved, centrifuging the solution until the solution is clear and transparent; Step S23: repeat step S22 to adjust the mass fraction of sodium alginate to 1.8%; Step S24: repeat step S22 to adjust the mass fraction of sodium alginate to 2.0%; The dissolution conditions were: magnetic stirrer 800 rpm, 30 min; the centrifugation conditions were: 37°C, 2500 rpm, 5 min.

[0026] Wherein, in step S3, the specific steps of preparing the gradient concentration ion solution are as follows: Step S31: Take 98% copper sulfate pentahydrate powder, add water to dissolve it, and prepare an ion solution with a concentration of 0.010M; Step S32: repeat step S31 and adjust the concentration to 0.015M; Step S33: Repeat step S31 and adjust the concentration to 0.020M.

[0027] Wherein, in step S4, the specific steps of preparing the gradient hydrogel system are as follows: Step S41: inject 200 μL of the ion solution obtained in step S33 into a transparent cylindrical mold with a bottom diameter of 10 mm and a height of 25 mm, then add 500 μL of the colloidal solution obtained in step S24 into the mold, and let it stand at 24° C. for 30 min to allow the copper ions to fully cross-link with the sodium alginate to form a bottom layer of hydrogel; Step S42: adding 200 L of the ion solution obtained in step S32 to the surface of the hydrogel obtained in step S41, and then adding 500 μL of the colloidal solution obtained in step S23, and standing at 24° C. for 30 min to allow the copper ions to fully cross-link with the sodium alginate to form a second layer of hydrogel; Step S43: adding 200 μL of the ion solution obtained in step S31 to the surface of the hydrogel obtained in step S42, and then adding 500 μL of the colloidal solution obtained in step S22, and standing at 24° C. for 30 min to allow the copper ions and sodium alginate to fully cross-link to form a gradient hydrogel system; Step S44: placing the hydrogel system obtained in step S43 into 2 mL of ultrapure water, and ultrasonically vibrating at 37° C. for 5 min, discarding the supernatant, removing the incompletely cross-linked copper ion solution, and obtaining a pure gradient hydrogel system; Step S45: sterilize the gradient hydrogel system obtained in step S44 under ultraviolet light irradiation; the environmental conditions of ultraviolet light irradiation are: at 24° C., wind speed of 0.2 m / s, and irradiation time of 8 h.

[0028] Wherein, in step S5, the specific steps of preparing the 3D printed porous screw are as follows: Step S51: Select the prepared PEI filaments, put them into an oven at 110° C., dry them for 2 hours, and then seal and store the dried PEI filaments; Step S52: According to the required shape of the screw, a pre-printed bracket structure model is established using a three-dimensional modeling software, and converted into an STL file that can be recognized in the 3D printing system; the obtained STL file is imported into the 3D printer system, and the print nozzle, print chamber, and molding substrate of the 3D printer are preheated through the automatic temperature control system, and then the PEI wire is fed into the preheated print nozzle through the automatic wire feeding device. The print nozzle prints layer by layer according to the trajectory path generated by the software until the printing is completed to obtain a 3D printed porous screw; the obtained 3D printed porous screw is placed in a 120°C oven and baked for 30 minutes.

[0029] Comparative Example 1: A titanium alloy screw with a gradient structure coating, comprising a titanium alloy screw and a bioactive component, wherein the bioactive component comprises: sodium alginate, copper sulfate, de-telopeptide type I collagen, zoledronic acid, chondroitin sulfate, and vascular endothelial growth factor (VEGF); wherein the concentration of copper sulfate is divided into three gradients, namely 0.010M, 0.015M, and 0.020M; the mass fraction of the sodium alginate solution is divided into three gradients, namely 1.5%, 1.8%, and 2.0%; the concentration of the de-telopeptide type I collagen solution is 1.0%; the concentration of zoledronic acid is 100 μM, and its main function is to promote the secretion of bone growth factor; the concentration of chondroitin sulfate is 100 mcg / mL, and its main function is to promote cartilage growth; the concentration of VEGF is 70 pg / ml, and its main function is to promote the vascularization process.

[0030] The method for preparing the titanium alloy screw with the gradient structure coating comprises the following specific steps: Step S1: weighing materials according to the gradient hydrogel system described above; Step S2: fully dissolving sodium alginate and atelocollagen type I at the above concentrations and mixing them to prepare a gradient concentration colloidal solution; Step S3: dissolving 98% copper sulfate pentahydrate powder in double distilled water at the above concentration to prepare a gradient concentration ion solution; Step S4: According to the concentrations of the three bioactive components, a gradient hydrogel system is prepared, which is specifically divided into three layers: The first layer: 1.5% sodium alginate + 1.0% atelocollagen type I + 0.010M copper sulfate solution + 70pg / mL VEGF solution; The second layer: 1.8% sodium alginate + 1.0% atelocollagen type I + 0.015M copper sulfate solution + 100mcg / mL chondroitin sulfate solution; The third layer: 2.0% sodium alginate + 1.0% atelocollagen type I + 0.020M copper sulfate solution + 100μM zoledronate solution; Using the cross-linking effect of copper sulfate and sodium alginate, gradient hydrogel structures with different cross-linking densities and different ion concentrations at different levels were prepared. The cross-linking conditions were as follows: the colloidal solution and the ion solution were fully mixed in turn according to different levels, and allowed to stand at 37°C for 30 minutes to achieve full cross-linking; Step S5: preparing a titanium alloy screw; Step S6: The gradient hydrogel system prepared in step S4 is wrapped on the surface of the titanium alloy screw prepared in step S5, and freeze-dried at -80°C for 36 hours.

[0031] Wherein, in step S2, the specific steps of preparing the gradient concentration colloidal solution are as follows: Step S21: Take the atelo-type I collagen powder, add water to dissolve it, prepare a solution with a mass fraction of 1.0%, and stir it at 24° C. for 10 minutes until the solution is clear and transparent; Step S22: Weigh sodium alginate powder and VEGF powder, add them to the solution obtained in step S21, and dissolve them into a solution with a sodium alginate mass fraction of 1.5% and a VEGF concentration of 70 pg / mL; the specific operation is: fully stir for 30 minutes at 24°C, add the powder while stirring to avoid powder agglomeration, and after the powder is fully dissolved, centrifuge the solution until the solution is clear and transparent; Step S23: Weigh sodium alginate powder and chondroitin sulfate powder, add them to the solution obtained in step S21, and dissolve them into a solution with a sodium alginate mass fraction of 1.8% and a chondroitin sulfate concentration of 100 mcg / mL. Stir thoroughly for 30 minutes at 24°C, adding the powder while stirring to avoid powder agglomeration. After the powder is fully dissolved, centrifuge the solution until the solution is clear and transparent. Step S24: weigh sodium alginate powder and zoledronate powder, add them to the solution obtained in step S21, and dissolve them into a solution with a sodium alginate mass fraction of 2.0% and a zoledronate concentration of 100 μM. Stir thoroughly for 30 minutes at 24° C., add the powder while stirring to avoid powder agglomeration. After the powder is fully dissolved, centrifuge the solution until the solution is clear and transparent. The dissolution conditions were: magnetic stirrer 800 rpm, 30 min; the centrifugation conditions were: 37°C, 2500 rpm, 5 min.

[0032] Wherein, in step S3, the specific steps of preparing the gradient concentration ion solution are as follows: Step S31: Take 98% copper sulfate pentahydrate powder, add water to dissolve it, and prepare an ion solution with a concentration of 0.010M.

[0033] Step S32: repeat step S31 and adjust the concentration to 0.015M; Step S33: Repeat step S31 and adjust the concentration to 0.020M.

[0034] Wherein, in step S4, the specific steps of preparing the gradient hydrogel system are as follows: Step S41: inject 200 μL of the solution obtained in step S33 into a transparent cylindrical mold with a bottom diameter of 10.0 mm and a height of 25 mm, then add 500 μL of the colloidal solution obtained in step S24 into the mold, and let it stand at 24° C. for 30 min to allow the copper ions to fully cross-link with the sodium alginate to form a bottom layer of hydrogel; Step S42: adding 200 L of the solution obtained in step S32 to the surface of the hydrogel obtained in step S41, and then adding 500 μL of the colloidal solution obtained in step S23, and standing at 24° C. for 30 min to allow the copper ions to fully cross-link with the sodium alginate to form a second layer of hydrogel; Step S43: adding 200 μL of the solution obtained in step S31 to the surface of the hydrogel obtained in step S42, and then adding 500 μL of the colloidal solution obtained in step S22, and standing at 24° C. for 30 min to allow the copper ions and sodium alginate to fully cross-link to form a gradient hydrogel system; Step S44: placing the hydrogel system obtained in step S43 into 2 mL of ultrapure water, and ultrasonically vibrating at 37° C. for 5 min, discarding the supernatant, removing the incompletely cross-linked copper ion solution, and obtaining a pure gradient hydrogel system; Step S45: sterilize the gradient hydrogel system obtained in step S44 under ultraviolet light irradiation; the environmental conditions of ultraviolet light irradiation are: at 24° C., wind speed of 0.2 m / s, and irradiation time of 8 h.

[0035] Wherein, in step S5, the specific steps of preparing the titanium alloy screw are as follows: Step S51: Select the prepared PEI filaments, put them into an oven at 110° C., dry them for 2 hours, and then seal and store the dried PEI filaments; Step S52: According to the shape of the required screw, a pre-printed bracket structure model is established using 3D modeling software, and converted into an STL file that can be recognized in the 3D printing system; the obtained STL file is imported into the 3D printer system, and the print nozzle, print chamber, and molding substrate of the 3D printer are preheated through the automatic temperature control system, and then the PEI wire is fed into the preheated print nozzle through the automatic wire feeding device. The print nozzle prints layer by layer according to the trajectory path generated by the software until the printing is completed to obtain a titanium alloy screw; the obtained titanium alloy screw is placed in a 100°C oven and baked for 30 minutes.

[0036] The three coatings of the gradient hydrogel system obtained in Example 1 and Comparative Example 1 were tested for stiffness performance, and the test results are shown in Table 1:

[0037] The data obtained in Table 1 reflect that the gradient hydrogel system has different biomechanical strengths at different levels. From the data in Table 1, it can be seen that the coating of the gradient hydrogel coating system is successfully constructed, which can simulate the different biological stress structures required for the growth of different bionic tissues. The data shown in Table 1 show that compared with the gradient hydrogel system in which other drugs are added in Comparative Example 1, the gradient hydrogel system in Example 1 has better biomechanical strength.

[0038] The structure of the 3D printed porous screw with gradient structure coating in Example 1 is as follows Figure 1 As shown, the gradient structure coated 3D printed porous screw consists of a 3D printed porous screw and three coatings on its outer side.

[0039] Rat mesenchymal stem cells were implanted on the surface of the screw system, and CCK proliferation biocompatibility tests were performed on the 3D printed porous screws with gradient structure coating in Example 1 on the 1st, 3rd and 5th days, respectively. The results are as follows: Figure 2 shown. Figure 2 It was shown that compared with the blank control group (Control), the three coatings of the gradient hydrogel system exhibited excellent biocompatibility.

[0040] Application Example 1: Twelve 12-week-old SD rats with an average body weight of 250 g were selected and divided into two groups, with 6 rats in each group. After the rats were anesthetized, a 1 cm incision was made at the lateral edge of the acromion, and a part of the deltoid muscle was cut to expose the acromion and supraspinatus tendon below, and the supraspinatus tendon was severed from the greater tuberosity. Holes were drilled in the rat footprint area, and the gradient hydrogel system (obtained from step S4 in Example 1) and the non-gradient hydrogel system (obtained from step S41 in Example 1) were implanted respectively, and the supraspinatus tendon was fixed in situ in the footprint area with sutures. The rats were killed 4 weeks later, and the maximum tensile load at the bone-tendon interface at the surgical site was measured. The results are as follows: Figure 3 shown. Figure 3 It was shown that the bone-tendon interface of rats implanted with gradient hydrogels exhibited a higher maximum tensile load compared with the non-gradient hydrogel system, indicating that the gradient hydrogel system can more effectively promote the healing of the bone-tendon interface.

[0041] Application Example 2: Twelve healthy New Zealand rabbits (12-16 weeks old, weighing 2.3-2.8 kg) were selected and divided into two groups, with 6 rabbits in each group. After the rabbits were anesthetized, a longitudinal incision was made on the posterior part of the calf to separate the flexor digitorum longus tendon with a length of 3 cm and a width of 2.5 mm as a tendon graft for anterior cruciate ligament reconstruction. A longitudinal incision of 2.5 cm in length was made with the ipsilateral patella as the center, the fascia was separated and the patella was pushed outward to expose the knee joint cavity and sever the anterior cruciate ligament. A bone tunnel was established along the starting and ending points of the original anterior cruciate ligament, the transplanted tendon was passed through the bone tunnel, and the graft was fixed using a 3D printed porous screw with a gradient structure coating (obtained from step S6 in Example 1) and a 3D printed porous screw with a non-gradient structure coating (obtained by freeze-drying the hydrogel obtained from step S41 of Example 1 on the surface of the porous screw obtained from step S5 of Example 1). The rabbits were killed after 6 weeks, and the maximum tensile load of the bone-tendon interface was measured. The results are as follows: Figure 4 shown. Figure 4 The results showed that compared with the 3D printed porous screws using non-gradient structural coatings, the samples of 3D printed porous screws using gradient structural coatings exhibited higher maximum tensile loads, indicating that the 3D printed porous screws with gradient structural coatings promoted the fixation of tendon tissue and the healing of the bone-tendon interface.

[0042] The above are only preferred embodiments of the present invention. It should be pointed out that, for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention. These should also be regarded as the protection scope of the present invention. These will not affect the effect of the implementation of the present invention and the practicality of the patent.

Claims

1. A 3D printed porous screw with a gradient structure coating, characterized in that: It includes 3D printed porous screws and bioactive ingredients, and the bioactive ingredients include sodium alginate, de-telopeptide type I collagen and divalent bioactive cations; wherein the mass fraction of the sodium alginate solution is divided into three gradients, namely 1.2-1.6%, 1.6-2.0%, and 2.0-2.4%; the concentration of the de-telopeptide type I collagen solution is 0.5-1.5%; the concentration of the divalent bioactive cations is divided into three gradients, namely 0.008-0.012M, 0.013-0.017M, and 0.018-0.022M; and the divalent bioactive cations are divalent copper ions.

2. A method for preparing a 3D printed porous screw with a gradient structure coating according to claim 1, characterized in that: The following steps are involved: Step S1: weighing materials according to the ratio; Step S2: fully dissolving sodium alginate and atelocollagen type I at the concentrations and mixing them to prepare a gradient concentration colloidal solution; Step S3: dissolving the divalent biologically active cations in double distilled water at the concentrations to prepare gradient concentration ion solutions; Step S4: According to the concentrations of the three bioactive components, a gradient hydrogel system is prepared, which is specifically divided into three layers: The first layer: 1.2~1.6% sodium alginate + 0.5~1.5% atelocollagen type I + 0.008~0.012M divalent bioactive cations; The second layer: 1.6~2.0% sodium alginate + 0.5~1.5% atelocollagen type I + 0.013~0.017M divalent bioactive cations; The third layer: 2.0~2.4% sodium alginate + 0.5~1.5% atelocollagen type I + 0.018~0.022M divalent bioactive cations; Step S5: preparing a 3D printed porous screw; Step S6: The gradient hydrogel system prepared in step S4 is wrapped on the surface of the 3D printed porous screw prepared in step S5, and freeze-dried at -80°C for 36 to 60 hours to complete the preparation of the 3D printed porous screw with a gradient structure coating.

3. The method for preparing a 3D printed porous screw with a gradient structure coating according to claim 2, characterized in that: In step S2, the specific steps of preparing the gradient concentration colloidal solution are as follows: Step S21: Take the atelo-type I collagen powder, add water to dissolve it, prepare a solution with a mass fraction of 0.5-1.5%, and stir it at 20-45° C. for 5-10 minutes until the solution is clear and transparent; Step S22: taking sodium alginate powder and adding it to the solution obtained in step S21 to prepare a solution with a mass fraction of sodium alginate of 1.2-1.6%; the specific operation is: stirring thoroughly for 20-40 minutes at 20-45°C, adding powder while stirring, and after the powder is fully dissolved, centrifuging the solution until the solution is clear and transparent; Step S23: repeat step S22 to adjust the mass fraction of sodium alginate to 1.6-2.0%; Step S24: repeat step S22 to adjust the mass fraction of sodium alginate to 2.0-2.4%; Dissolution conditions were: magnetic stirrer 500-1000 rpm, 20-40 min; The centrifugation conditions were: 37°C, 2500 rpm, 5-10 min.

4. The method for preparing a 3D printed porous screw with a gradient structure coating according to claim 3, characterized in that: In step S3, the specific steps of preparing the gradient concentration ion solution are as follows: Step S31: taking a divalent biologically active cation powder, adding water to dissolve it, and preparing an ion solution with a concentration of 0.008-0.012M; Step S32: repeat step S31 to adjust the concentration to 0.008-0.012M; Step S33: Repeat step S31 to adjust the concentration to 0.018~0.022M.

5. The method for preparing a 3D printed porous screw with a gradient structure coating according to claim 4, characterized in that: In step S4, the specific steps of preparing the gradient hydrogel system are as follows: Step S41: inject 200-300 μL of the ion solution obtained in step S33 into a transparent cylindrical mold with a bottom diameter of 10-15 mm and a height of 25-35 mm, then add 500-800 μL of the colloidal solution obtained in step S24 into the mold, and let stand at 24-37° C. for 20-45 min to form a bottom layer of hydrogel; Step S42: adding 200-300 μL of the ion solution obtained in step S32 to the surface of the hydrogel obtained in step S41, and then adding 500-800 μL of the colloidal solution obtained in step S23, and standing at 24-37° C. for 20-45 min to form a second layer of hydrogel; Step S43: adding 200-300 μL of the ion solution obtained in step S31 to the surface of the hydrogel obtained in step S42, and then adding 500-800 μL of the colloidal solution obtained in step S22, and standing at 24-37° C. for 20-45 min to form a gradient hydrogel system; Step S44: placing the gradient hydrogel system obtained in step S43 into 2-2.5 mL of ultrapure water, ultrasonically vibrating for 5-10 min at 24-37° C., discarding the supernatant, and obtaining a pure gradient hydrogel system; Step S45: placing the gradient hydrogel system obtained in step S44 under ultraviolet light for sterilization; the environmental conditions for ultraviolet light irradiation are: temperature of 24-37° C., wind speed of 0.2-0.4 m / s, and irradiation time of 8-12 h.

6. The method for preparing a 3D printed porous screw with a gradient structure coating according to claim 1, characterized in that: In step S5, the specific steps of preparing the 3D printed porous screw are as follows: Step S51: Select the prepared PEI filaments, put them into an oven at 110-130° C., dry them for 2 hours, and then seal and store the dried PEI filaments; Step S52: According to the shape of the required screw, a pre-printed bracket structure model is established using a three-dimensional modeling software, and the model is converted into an STL file; the STL file is imported into the 3D printer system, and the print nozzle, print chamber and molding substrate of the 3D printer are preheated through the automatic temperature control system, and then the PEI wire is fed into the preheated print nozzle using an automatic wire feeding device. The print nozzle prints layer by layer according to the trajectory path generated by the software until the printing is completed to obtain a 3D printed porous screw; the obtained 3D printed porous screw is placed in an oven at 100-120°C and baked for 10-30 minutes.

Citation Information

Patent Citations

  • Application of poly(lactic-co-glycolic acid) scaffold in promoting cartilage differentiation and regeneration

    CN116870249B

  • Preparation method of titanium surface nano composite coating for promoting osteogenesis

    CN118987338A

  • Polysaccharide-based nerve repair stent material with continuous gradient property and preparation method thereof

    CN102198291A

  • Photo-crosslinking multilayer gradient hydrogel capable of controllably releasing active factors and preparation method of hydrogel

    CN103721293A

  • Three-layer blood vessel containing compact endodermis as well as preparation method and application of three-layer blood vessel

    CN118652838A